A atuação profissional do serviço social no acompanhamento das famílias do benefício de prestação continuada – BPC em Abaetetuba – Pará - GALVÃO, Sylmara Corrêa (2023)
The present study analyzes the professional performance of Social Service in the care as families using the Benefit Continuous Provision - BCP. In order to join the research object, a study of the history of theories such as liberalism, Keynesianism / Fordism, Welfare State (Welfare State) was developed. Later, the historical context of social policies in the different Brazilian governments was analyzed, emphasizing the advances / achievements and setbacks in the field of social rights. The Social Service's professional activity was focused on guaranteeing social rights, emphasizing the theoretical wording of the Ethical-Political Project of Social Service and the discussion about professional projects and corporate projects.The family category and its new configurations in contemporary society were approached and problematized as a field of action for social workers and the holder of rights derived from social policies, but the fruits of many struggles of the working class and their representative entities. Finally, the BPC was emphasized, seeking to capture and construct information about the process of granting this benefit by the professionals included in the Social Assistance Policy, as well as the analysis of this benefit on the users' perspective. In order to capture and construct information, in addition to the basis of productions that approach BPC critically, forms were applied to users and professionals for the quantitative and qualitative collection of data.